Security operations management. - McCrie, Robert D.; Lee, Seungmug (Butterworth-Heinemann, 2022)
Security Operations Management, Fourth Edition, the latest release in this seminal reference on corporate security management operations for today's security management professionals and students, explores the characteristics of today's globalized workplaces, security's key role within them, and what the greatest concern is for security practitioners and senior managers. Incorporating the latest security research and best practices, the book covers key skills needed by security managers to demonstrate the value of their security program, offers information on identifying and managing risk, and reviews the latest technological advances in security control, command, communications and computing.